2023
DOI: 10.1002/adma.202304069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zwitterionic CsPbBr3 Nanocrystals with Controlled Anisotropy using Surface‐Selective Ligand Pairs

Abstract: Mechanistic studies of the morphology of lead halide perovskite nanocrystals (LHP‐NCs) are hampered by a lack of generalizable suitable synthetic strategies and ligand systems. Here, the synthesis of zwitterionic CsPbBr3 NCs is presented with controlled anisotropy using a proposed “surface‐selective ligand pairs” strategy. Such a strategy provides a platform to systematically study the binding affinity of capping ligand pairs and the resulting LHP morphologies. By using zwitterionic ligands (ZwL) with varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Other short ligands with stronger interactions with PQDs should be explored. For example, the zwitterionic ligand 92–94 can tightly bound with the PQDs via the chelate effect, while the co-occurrences of cationic and anionic groups can prevent the external neutralization surroundings of PQDs, and thus enhance the structural durability of PQD films. Therefore, zwitterionic ligands should be further explored for application in solar cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other short ligands with stronger interactions with PQDs should be explored. For example, the zwitterionic ligand 92–94 can tightly bound with the PQDs via the chelate effect, while the co-occurrences of cationic and anionic groups can prevent the external neutralization surroundings of PQDs, and thus enhance the structural durability of PQD films. Therefore, zwitterionic ligands should be further explored for application in solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another family of X-type ligands that has received much attention is zwitterionic (or bidentate) ligands, in which the two functional groups with negative and positive charges simultaneously bind to the X-site and A-site, respectively. 61,62,92–94 The long-chain zwitterionic ligands include sulfabetaine, phosphocholine, and γ-amino acid92 (Fig. 8c).…”
Section: Surface Engineering Of Pqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the need for the molecular engineering of zwitterionic ligands. Various kinds of zwitterionic ligands such as aromatic [141], polymeric [150][151][152], photo-crosslinkable [153], amino acids [154], modular zwitterion functionalized polymers [155], carbazole [156], and quaternary ammonium halide-based zwitterionic ligands [157] show an important role in stabilizing highly luminescent Cs LHP NCs are explored. Interestingly, Zhu et al have proposed that both surface-selective and non-selective ligands are necessary to control the morphology and stability of CsPbBr 3 NCs [157].…”
Section: Potential Ligands and Solvents Replacing Oa And Oam: A Step ...mentioning
confidence: 99%
“…Various kinds of zwitterionic ligands such as aromatic [141], polymeric [150][151][152], photo-crosslinkable [153], amino acids [154], modular zwitterion functionalized polymers [155], carbazole [156], and quaternary ammonium halide-based zwitterionic ligands [157] show an important role in stabilizing highly luminescent Cs LHP NCs are explored. Interestingly, Zhu et al have proposed that both surface-selective and non-selective ligands are necessary to control the morphology and stability of CsPbBr 3 NCs [157]. The authors have demonstrated that zwitterionic ligands are surface-selective to achieve anisotropic nanostructures (nanocubes, NPLs and NRs), and didecylamine (DDA)-based surface non-selective ligands could assist for it along with stability.…”
Section: Potential Ligands and Solvents Replacing Oa And Oam: A Step ...mentioning
confidence: 99%